Drug delivery systems obtained from silica based organic-inorganic hybrids - Oshiro, João Augusto [UNESP]; Abuçafy, Marina Paiva [UNESP]; Manaia, Eloísa Berbel [UNESP]; Da Silva, Bruna Lallo [UNESP]; Chiari-Andréo, Bruna Galdorfini [UNESP]; Chiavacci, Leila Aparecida [UNESP] (MDPI, 2016)
This is a review of hybrid materials based on silica as an inorganic phase used as drug delivery systems (DDS). Silica based DDS have shown effectivity when compared with traditional delivery systems. They present advantages such as: (a) ability to maintain the therapeutic range with minor variations; (b) prevention of local and systemic toxic effects; (c) plasma concentrations increase of substances with a short half-life; and (d) reduction of the number of daily doses, which may increase patient adherence to the treatment. These advantages occur due to the physical, chemical and optical properties of these materials. Therefore, we discuss the properties and characteristics of them and we present some applications, using different approaches of DDS to ensure therapeutic effectiveness and side effects reduction such as implantable biomaterial, film-forming materials, stimuli-responsive systems and others.
Keywords: Drug delivery systems; Organic-inorganic materials; Sol-gel process